The Relationship between Resilience and Academic Procrastination seen from Students’ Self-Compassion - Rahmatia, Rahmatia; Eddy Wibowo, Mungin; Sunawan, Sunawan (Jurnal Bimbingan Konseling, 2022)
Academic procrastination hampers students’ achievement. Thus, the current research identified and analyzed the relationship between resilience and academic procrastination with self-compassion as the mediator by involving Junior High School students (SMP Negeri) throughout Tolitoli City as many as 326 people chosen using cluster random sampling. Their data were collected using the scales of resilience, academic procrastination, and self-compassion. Findings showed a direct negative relationship between resilience and academic procrastination, self-compassion had a positive relationship with resilience, and academic procrastination negatively related to self-compassion. Further, based on the mediation analysis the researchers found no direct relationship between resilience and academic procrastination through self-compassion. These imply that reducing academic procrastination is important to imptove self-compassion and resilience.